The disabled tourist : navigating an ableist tourism world - Gillovic, Brielle; McIntosh, Alison; Darcy, Simon (The tourist experience, 2024)
This book addresses a growing demand to hear the authentic voices and understand the lived tourist experiences of people with disability. The latest volume in The Tourist Experience series challenges what is arguably an exclusionary, marginalising, discriminatory, and ableist (tourism) world. By drawing attention to the 'dis/' in 'disabled', the authors provoke the need to change binary thinking about people who live with disability so that they may be 'able' to assume the role of tourist. They engage critical tourism and critical disability studies, and their respective theories, perspectives, and debates, around, for instance, models of disability that shape conceptualisations and worldviews, inclusive research and enabling language, and the ethics of care. These are pivotal to dismantling normative structures to enable a more inclusive, equitable, and socially just tourist experience that promotes a more independent and dignified tourism world for people with disability.